Beban Kerja Karyawan - Siti Ila Sulaila; Tini Kartini (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Workload management is a critical issue in the banking sector due to high service intensity and time pressure faced by frontline employees. An imbalance between job demands and employee capacity may lead to work fatigue and reduced service quality. This study aims to analyze employee workload and identify workload indicators that require managerial attention in order to support effective human resource management. A qualitative descriptive approach was employed, with data collected through direct observation, in-depth interviews, and documentation. Employee workload was analyzed using five indicators: task quantity, task complexity, time required, task frequency, and task variability. The findings indicate that workload conditions are generally appropriate in terms of task quantity, task complexity, and task variability, reflecting alignment with job descriptions and existing work systems. However, the indicators of time required and task frequency reveal relatively high workload levels, particularly for customer service and teller positions, due to limited staffing and fluctuating customer volume. These conditions potentially increase work fatigue and reduce service effectiveness. Therefore, this study highlights the importance of evaluating workload distribution and optimizing human resource planning to ensure a balance between service demands and employee capacity in the banking sector.